Genetic variants in CYP4F2 were significantly correlated with susceptibility to ischemic stroke - Wu, Yuan (BMC Med Genet, 2019)
BACKGROUND: Ischemic stroke (IS) is a serious cardiovascular disease and is associated with several single nucleotide polymorphisms (SNPs). However, the role of Cytochrome P450 family 4 subfamily F member 2 (CYP4F2) gene in IS remains unknown. Our study aimed to explore whether CYP4F2 polymorphisms influenced IS risk in the Han Chinese population. METHODS: We selected 477 patients and 495 controls to do a case-control study, and five SNPs in CYP4F2 gene were successfully genotyped. And we evaluated the associations using the Chi-squared test, independent sample t test, and genetic models analyses. Logistic regression analysis was used to calculate odds ratios (ORs) and 95% confidence intervals (CIs). RESULTS: In this study, rs12459936 and rs3093144 were associated with IS risk in the overall. After stratified analysis by age (> 61 years), rs3093193 and rs3093144 were related to an increased risk of IS, whereas rs12459936 was related to a decreased risk of IS. In addition, we found that three SNPs (rs3093193, rs3093144 and rs12459936) were associated with the susceptibility to IS in males. We also found five SNPs in the CYP4F2 gene had strong linkage. CONCLUSIONS: Three SNPs (rs3093193, rs3093144 and rs12459936) in the CYP4F2 were associated with IS risk in a Chinese Han population. And, CYP4F2 gene may be involved in the development of IS. SUPPLEMENTARY INFORMATION: Supplementary information accompanies this paper at (10.1186/s12881-019-0888-6).